Pentingnya Enterpreneurship: Kegiatan Pengabdian Pada Sekolah Lansia Bekasi - Julisar; Haryanti, Denny Septa; Indriyanti, Irma Satya; Ponziani, Regi Muzio; Soegijanto, Cleophila M. G. T.; Sunny, Gloria Christina; Hidayat, Muwafick (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2025)
This community service activity aims to elaborate the importance of entrepreneurship and to motivate the students of Sekolah Lansia Bekasi to become more independent after undergoing pension. The theme of the community service activity is Entrepreneurship and was conducted on 22 January 2025, 09.00 until 11.30 in kecamatan Rawa Lumbu, Kotamadya Bekasi. The activity was attended by 270 students. The activity was opened by opening speech by the headmaster of Sekolah Lansia Bekasi, Ibu Sri Kustini. After that the Secretary for the Center of Research and Community Service Trisakti School of Management (TSM), Regi Muzio Ponziani, delivered a speech. Only then did the speakers that were also the lecturers of TSM delivered the community service materials.